2014
DOI: 10.1371/journal.pone.0108547
|View full text |Cite
|
Sign up to set email alerts
|

Single Muscle Fiber Gene Expression with Run Taper

Abstract: This study evaluated gene expression changes in gastrocnemius slow-twitch myosin heavy chain I (MHC I) and fast-twitch (MHC IIa) muscle fibers of collegiate cross-country runners (n = 6, 20±1 y, VO2max = 70±1 ml•kg−1•min−1) during two distinct training phases. In a controlled environment, runners performed identical 8 kilometer runs (30∶18±0∶30 min:s, 89±1% HRmax) while in heavy training (∼72 km/wk) and following a 3 wk taper. Training volume during the taper leading into peak competition was reduced ∼50% whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…Consistent with the idea that MyHC IIa fibers are especially sensitive to heavy training, MyHC IIa fibers undergo substantial remodeling when provided with a period of recovery (Trappe et al, 2000, 2006; Neary et al, 2003; Luden et al, 2010). More specific to the myogenic program, the induction of FN14 mRNA following running exercise was suppressed in MyHC IIa muscle fibers relative to the response elicited after 3 weeks of tapered training (Murach et al, 2014). This is relevant here because FN14 and the associated TWEAK pathway have been implicated in the regulation of myogenesis (Enwere et al, 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the idea that MyHC IIa fibers are especially sensitive to heavy training, MyHC IIa fibers undergo substantial remodeling when provided with a period of recovery (Trappe et al, 2000, 2006; Neary et al, 2003; Luden et al, 2010). More specific to the myogenic program, the induction of FN14 mRNA following running exercise was suppressed in MyHC IIa muscle fibers relative to the response elicited after 3 weeks of tapered training (Murach et al, 2014). This is relevant here because FN14 and the associated TWEAK pathway have been implicated in the regulation of myogenesis (Enwere et al, 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, taper's efficacy has been well documented in swimming, cycling, running, triathlon, rowing, strength training, and team sports to name a few. The effects of tapering are apparent from the whole body (macro) [4] to the cell and gene (micro) [5,6] levels and even include psychological improvements [7]. Despite the multitude of data supporting taper's effectiveness, some athletes and coaches still fail to acknowledge its importance and implement the practice.…”
Section: Open Accessmentioning
confidence: 99%
“…However, the literature indicates that fitness in endurance athletes (measured as aerobic capacity, or VO2max) is not lost following the taper period and five studies have actually shown an increase in fitness with less training [18,[21][22][23]25]. Reducing training volume for as long as four weeks [7] by >85% (in the last week) [6,19] still yields gains in performance without a loss of fitness. Considering the robust adaptations observed with short-duration high-intensity interval training, even in already highly trained individuals [26,27], it should come as no surprise that a well-designed taper of reduced volume and quality high intensity work can preserve fitness for up to a month.…”
Section: Fitness Is Not Lost With Tapermentioning
confidence: 99%
See 2 more Smart Citations